2010
DOI: 10.1016/j.yexcr.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

SAM pointed domain ETS factor (SPDEF) regulates terminal differentiation and maturation of intestinal goblet cells

Abstract: Background & Aims: SPDEF (also termed PDEF or PSE), is an ETS family transcription factor that regulates gene expression in the prostate and goblet cell hyperplasia in the lung. Spdef has been reported to be expressed in the intestine. In this paper, we identify an important role for Spdef in regulating intestinal epithelial cell homeostasis and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(188 citation statements)
references
References 43 publications
14
172
2
Order By: Relevance
“…Thus, in Mek1DD; Shp2 double mutant mice, goblet cells are rescued, and this appears to occur at the expense of paneth cells. This is reminiscent of the phenotype observed after overexpression of the Ets transcription factor Spdef; Spdef overexpression promoted goblet cell differentiation at the expense of paneth cells (22). In control mice, goblet and paneth cells produce the Ets transcription factor Spdef, as assessed by IHC (Fig.…”
Section: Ablation Of Shp2 Induces Premature Differentiation Of Panethmentioning
confidence: 61%
See 2 more Smart Citations
“…Thus, in Mek1DD; Shp2 double mutant mice, goblet cells are rescued, and this appears to occur at the expense of paneth cells. This is reminiscent of the phenotype observed after overexpression of the Ets transcription factor Spdef; Spdef overexpression promoted goblet cell differentiation at the expense of paneth cells (22). In control mice, goblet and paneth cells produce the Ets transcription factor Spdef, as assessed by IHC (Fig.…”
Section: Ablation Of Shp2 Induces Premature Differentiation Of Panethmentioning
confidence: 61%
“…1 A and B). The intervention was accompanied by a drop in mRNAs of Spdef, Muc2, and Gob5, which are typically expressed in goblet cells (21)(22)(23), as assessed by qRT-PCR ( Fig. 1 C and D).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with previous studies demonstrating that overexpression of IL-13 in the pulmonary compartment induces mucus hypersecretion (38 -40). Goblet cell differentiation in both the lung and intestine is thought to be regulated by the sterile ␣-motif-pointed domain-containing Ets-like factor (SPEDF) (41)(42)(43). Employing the lung-specific inducible IL-13 transgenic mice CCSP-rtTA/tet0-CMV-IL-13, investigators demonstrated that pulmonary IL-13-induced goblet cell hyperplasia is associated with induction of SPDEF expression (44).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we examined the expression of mRNA for Muc2, Agr2, and the goblet cell transcription factor Spdef (Park et al, 2007;Gregorieff et al, 2009;Noah et al, 2010). Spdef and Muc2 were significantly decreased in Winnie Consistent with the AB staining, in the proximal and mid colon, the decrease in Muc2 precursor accumulation was less than in the distal colon.…”
Section: Glucocorticoids Suppress Er Stress and Restore Mature Muc2 Bmentioning
confidence: 74%